Analisis Persepsi Wisatawan Terhadap Potensi Penerapan Qris Di Pulau Karampuang - Hasrawati; Liravirna; Hari Yeni (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze tourists’ perceptions of the potential implementation of the Quick Response Code Indonesian Standard (QRIS) in improving transaction efficiency and tourist satisfaction on Karampuang Island, considering the continued dominance of cash-based transactions that are perceived as inefficient and reduce transaction convenience. This research employs a quantitative approach using a survey method involving 43 tourists selected through purposive sampling. The research variables include perceived ease of use, perceived usefulness, perceived security of QRIS, as well as perceptions of transaction efficiency and tourist satisfaction, which were analyzed using descriptive statistics, validity and reliability tests, and a One-Sample t-Test with the assistance of SPSS. The results indicate that tourists have positive perceptions of the potential implementation of QRIS, which is perceived to enhance transaction efficiency through faster and more practical payment processes while providing security and convenience that contribute to tourist satisfaction, indicating that QRIS has strong potential to be implemented on Karampuang Island to improve the quality of tourism services.